Aplikasi Database Untuk Mengelola Persediaan Barang di Toko Baju D’Clothing Menggunakan Pendekatan Entity Relationship Chart - Zerlinda, Frea Marva; Zulfa Zaidan, Muhammad; Fisrawati; Hadias Safitri, Novia; Fathan Nabil Al-Badi, Muhammad (Jurnal Sains Indonesia, 2023)
D’Clothing store is one of the clothing stores located in Bogor that provides many choices for various ages, both women and men. Based on the interviews, D'Clothing store had some troubles in product management, starting from inventory data, suppliers data, sales data, et cetera. To overcome this problem, a new system is needed to facilitate management by utilizing technological products, which as creating a database. The output of this database is to make a form containing the name, stock, color, size, code, and price of the goods. In its preparation, there are several obstacles such as data being out of sync between the main table and other tables when building a relationship. After being analyzed, this issue happens due to the wrong placement of the primary key and records between tables. Another error is found in the placement of the formula when building the Query design. Therefore, it takes precision and logic to find a way out.